Verbal Humor in Louis C.K.â€™S Stand-Up Comedy Concert â€œOh My Godâ€: The Pragmatic Strategies - Syauqillah, Uda Makiyya; Setyaningsih, Nina (Allure Journal, 2022)
A stand-up comedy performance is not only about amusing the audiences with the joke, but it also has other functions. This research analyzes the pragmatic strategies and function of Louis C.K.â€™s stand-up comedy concert â€œOh My Godâ€. Raskin and Attardoâ€™s (1992) General Theory of Verbal Humor (GTVH) and Griceâ€™s (1975) maxims of cooperative principle were employed as the framework of the analysis. A descriptive qualitative method was also used to analyze the data. The result reveals that Louis C.K.â€™s jokes in this concert mostly violate the maxim of quantity to generate laughter through exaggeration and faulty reason. Furthermore, Louis C.K.â€™s stand-up comedy is not only a way to entertain but it also has another function, that is, to deliver certain messages to the audience. Louis C.K.â€™s joke is also a form of giving a narrative to the audiences to understand the reality that people face in another point of view.